ANALISIS PERAN AYAH TERHADAP PENGASUHAN ANAK DALAM MEMBANGUN KETAHANAN KELUARGA SEBAGAI PONDASI KETAHANAN NASIONAL - Marwah Insan, Hakimah (Program Studi Hukum Tata Negara, 2021)
This study aims to determine how the role of fathers in child care. This study uses a qualitative method with a case study approach. The participants of this study were pre-adolescent children 6-12 years and adolescents 18-21 years. Data collection was carried out by in-depth interview method. Therefore, infortifying children from influences that will later have a negatif effect on children by strengthening religious issue, how to choose good friend because if the child has good friend it will also have a good effect on the child but if the child chooses the wrong friend then the child will also fall into problems that result in less good for the child’s future